La teoría mimética aplicada a las relaciones interpersonales a través de redes sociales: el caso de piñagate en Mercadona. - Paradinas Márquez, María del Carmen; Marín-Palacios, Cristina (Revista Latina de Comunicación Social, 2026)
Introduction: Piñagate illustrates how social networks amplify mimetic behaviours. It analyses how desires and behaviours are digitally replicated, highlighting the role of tweets and viral content in their expansion. This case provides new perspectives on mimetic theory applied to digital phenomena and its impact on contemporary communication. Methodology: The analysis was carried out by collecting tweets with 'pineapple' AND 'Mercadona' AND 'flirt'. After data cleaning in Excel and Google Colab, a sentiment analysis was carried out with Pipeline (Transformers) to subsequently extract keywords with NLTK and elaborate thematic maps with VOSviewer. Results: The results indicate that the content of the tweets analysed has a positive tone or a favourable response from the community analysed. Four groups are identified: General Context of Mercadona, Strategies for Flirting, Environments and Products, and Moments and Occasions. Discussion: The application of mimetic theory to social networks has generated both interest and criticism. Some argue that it provides a valuable explanation for understanding online behaviour and group dynamics. However, others criticise that it may oversimplify the complexity of human interactions and individual motivations. Conclusions: The piñagate at Mercadona illustrates how mimetic theory explains viral phenomena in social networks, highlighting how trivial symbols, such as a pineapple, are transformed into acts of interpersonal communication. This study combines data analysis and natural language, showing how digital culture redefines social norms and commercial perceptions.